2002
DOI: 10.1016/s0304-3959(02)00069-6
|View full text |Cite
|
Sign up to set email alerts
|

Interference due to pain following spinal cord injury: important predictors and impact on quality of life

Abstract: Two studies were designed to examine important predictors of pain following spinal cord injury (SCI), and the impact of pain on self-reported quality of life (QOL). Pain was defined as "interference in day-to-day activities secondary to pain". In order to determine risk factors associated with the development of pain interference, Study 1 examined the predictive validity of multiple demographic, medical, and QOL variables at year 1 post-SCI to self-reported pain interference 2 years post-injury. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 43 publications
7
101
1
1
Order By: Relevance
“…As one of the major consequences of SCI, pain has been found to affect quality of life, [1][2][3][4][5][6] leisure time activities, 5,7 vocational status, 7,8 and sexuality. 9 In non-SCI populations, poor sleep quality has been found in patients suffering from different health conditions such as obstructive pulmonary diseases, diabetes, rheumatic diseases, 10 and chronic pain conditions [11][12][13][14] as well as in patients suffering from affective disorders.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the major consequences of SCI, pain has been found to affect quality of life, [1][2][3][4][5][6] leisure time activities, 5,7 vocational status, 7,8 and sexuality. 9 In non-SCI populations, poor sleep quality has been found in patients suffering from different health conditions such as obstructive pulmonary diseases, diabetes, rheumatic diseases, 10 and chronic pain conditions [11][12][13][14] as well as in patients suffering from affective disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Pain has been found to negatively impact the physical and emotional health and quality of life of individuals with a SCI. [22][23][24] Although there are many definitions of community integration, each includes the idea of participation and involvement in one's roles and activities. 25 Therefore, it may be this direct influence of pain on the physical and emotional dimensions of an individual that are indirectly influencing an individual's ability to fully integrate into their community.…”
Section: Discussionmentioning
confidence: 99%
“…Shechtman (22) reported that shoulder pain was associated with age for a wheelchair user group compared with an able-bodied group. Putzke et al (16) noted lower pain levels in younger and older subjects, whereas Salisbury et al (24) noted just the opposite, with lower pain in middle-aged subjects. However, separating age and time spent in a wheelchair is difficult, and several studies noted no relationship between these factors and pain in the UEs.…”
Section: Introductionmentioning
confidence: 96%
“…Nearly 94% of people with SCI reported pain in the UEs at some time, (16) with 70% reporting current UE pain (17,18). The most common site is the shoulder followed by wrists and hands (2,6,19).…”
Section: Introductionmentioning
confidence: 99%